The fire next time eaudiobook - Baldwin, James (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2008)
NATIONAL BESTSELLER - The book that galvanized the nation, gave voice to the emerging civil rights movement in the 1960s—and still lights the way to understanding race in America today. - "The finest essay I've ever read." —Ta-Nehisi CoatesAt once a powerful evocation of James Baldwin's early life in Harlem and a disturbing examination of the consequences of racial injustice, the book is an intensely personal and provocative document from the iconic author of If Beale Street Could Talk and Go Tell It on the Mountain. It consists of two "letters," written on the occasion of the centennial of the Emancipation Proclamation, that exhort Americans, both black and white, to attack the terrible legacy of racism. Described by The New York Times Book Review as "sermon, ultimatum, confession, deposition, testament, and chronicle ... all presented in searing, brilliant prose," The Fire Next Time stands as a classic of literature.